2021
DOI: 10.1111/aej.12572
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of transforming growth factor‐beta 1 (TGF‐β1) on human apical papilla cell proliferation and mineralisation

Abstract: Firstly, this study investigated the direct effect of Transforming Growth Factorbeta 1 at 10, 5, 2.5 and 1.25 ng mL À1 on human apical papilla cell proliferation and mineralisation. Cell proliferation was examined at 0, 2, 4, 6, 24, 48, 72, 96 and 120 h using Alamar Blue TM assay. Cell mineralisation was examined at day 21 with a quantitative Alizarin Red S staining. Secondly, the study aimed to estimate the amount of Transforming Growth Factor-beta 1 (TGF-b1) released from the dentin after root canal irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…TGF-β1 was quantified using ELISA following the canal irrigation procedure. This approach aligns with prior research, as measuring growth factors post-irrigation mirrors the clinical scenario where bleeding is induced at the apex after irrigation and drying [ 6 , 14 , 45 ]. This differs from the study by Galler et al, where growth factor release was measured during irrigation [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…TGF-β1 was quantified using ELISA following the canal irrigation procedure. This approach aligns with prior research, as measuring growth factors post-irrigation mirrors the clinical scenario where bleeding is induced at the apex after irrigation and drying [ 6 , 14 , 45 ]. This differs from the study by Galler et al, where growth factor release was measured during irrigation [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…SCAPs express the TGF-β receptor 1 [10], suggesting they can receive regulation from TGF-β ligands. Secreted TGF-β1 and TGF-β2 are embedded in the dentin during tooth development, and they can release from the dentin during endodontic procedures, such as root canal therapy [41][42][43]. Studies have demonstrated that TGF-β1 can inhibit the proliferation, differentiation, and mineralization of SCAPs in dose-dependent and Smad3-dependent manners [41,44].…”
Section: Transforming Growth Factor-b Superfamilymentioning
confidence: 99%
“…Secreted TGF-β1 and TGF-β2 are embedded in the dentin during tooth development, and they can release from the dentin during endodontic procedures, such as root canal therapy [41][42][43]. Studies have demonstrated that TGF-β1 can inhibit the proliferation, differentiation, and mineralization of SCAPs in dose-dependent and Smad3-dependent manners [41,44]. Interestingly, TGF-β1 inhibits the odontogenic differentiation of SCAPs while enhancing their osteogenic differentiation.…”
Section: Transforming Growth Factor-b Superfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…Pertaining to bone formation, they trigger signaling for BMPs production in osteoprogenitor cells, promote osteogenic differentiation, angiogenesis, prevent osteoclast activation, and promote osteoclast apoptosis [105] , [106] . In dentin forming aspect, TGF-β1 can promote apical papilla cell proliferation and mineralization [107] . TGF-β2 can regulates tooth root dentinogenesis by cooperation with Wnt signaling [108] .…”
Section: Dynamic Transfer Process Of Mineralsmentioning
confidence: 99%